2012
DOI: 10.1007/s00038-012-0358-9
|View full text |Cite
|
Sign up to set email alerts
|

Joint trajectories of multiple health-related behaviors among the elderly

Abstract: The nature of healthy behaviors and risky behaviors may differ. Thus, multiple trajectories can exhibit patterns that differ from those of single behavior trajectories. Strategies designed to promote health need to consider both gender and behavior patterns which may change over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 38 publications
12
34
2
Order By: Relevance
“…The present results show that the “Inactives” cluster was characterized by socially inactive participants, whose estimated probability of weekly physical activity was lower than the other two clusters; yet they neither smoked nor drunk alcohol excessively. Comparable clusters characterized by insufficient physical activity with no other risk behaviors have been found in German and Taiwanese middle‐ to older‐aged samples, with no indicators of participants’ social activity levels. Current health promotion programs mainly focus on smoking, drinking and physical activity, which appears less relevant to this group .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The present results show that the “Inactives” cluster was characterized by socially inactive participants, whose estimated probability of weekly physical activity was lower than the other two clusters; yet they neither smoked nor drunk alcohol excessively. Comparable clusters characterized by insufficient physical activity with no other risk behaviors have been found in German and Taiwanese middle‐ to older‐aged samples, with no indicators of participants’ social activity levels. Current health promotion programs mainly focus on smoking, drinking and physical activity, which appears less relevant to this group .…”
Section: Discussionmentioning
confidence: 92%
“…The variation in gendered cluster patterns identified here are consistent with the literature. For example, research has found a much lower prevalence of current smoking and alcohol consumption in older Asian women than men, resulting from traditional social norms and cultural constraints . In contrast, there is a convergence in alcohol consumption between Western women and men, mainly due to increased consumption amongst women …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to also include the following explanatory variables, based on previous studies: sex, education level, urbanization, marital status, smoking, leisure time physical activity, and body mass index (BMI) (Chen et al 2007;Hsu et al 2013;Ishizaki et al 2009;Mantzavinis et al 2005;Sodergren et al 2008). These variables were measured in each survey and included in the models as time-varying covariates.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Another methodological issue when studying SRH trends is to control for potential confounding factors (Ishizaki et al 2009;Mantzavinis et al 2005). SRH has been associated with several variables, such as gender (af Sillen et al 2005), age (Idler 1993), sociodemographic factors (Kachi et al 2013;Sacker et al 2011), and lifestyle factors (Hsu et al 2013;Sodergren et al 2008). …”
Section: Introductionmentioning
confidence: 99%